Seasonal influences on gonadal and extragonadal sperm reserves in Small East African Zebu (Bos indicus) bulls in Ethiopia - Tegegne, Azage; Entwistle, K.W.; Mukasa-Mugerwa, E. (Springer, 1992)
Analyses data by analysis of variance to determine seasonal effects on reproductive capacity using the General Linear Models (GLM) procedures of the SAS Programme (SAS, 1987). Body weight was used as a covariate. Polynomial regression analysis was done to determine relationships between body and testicular traits. Evaluates correlation coefficients between body and testicular triats. Presents data on body weight and reproductive characteristics. Significant correlation coefficients among the various traits are presented by season in Table II. Bulls slaughtered during the dry season were significantly (P<0.001) lighter and had significantly (P<0.001) smaller SC measurements than those slaughtered during the wet season. Presents the relationship between body weight and scrotal circumferences, between scrotal circumference and paired testes weight, between scrotal circumference and daily sperm production (DSP) and the relationships between paired testes weight and daily sperm production along with their respective production equations in mature small East African zebu bulls.